SCREENING AND PRODUCTION OF ANTICARCINOGENIC ENZYME FROM ESCHERICHIA COLI CTLS20: L - ASPARAGINASE - Thandeeswaran, Murugesan; Mahendran, Ramasamy; Kiran, Kalarikkal Gopikrishnan; Nawaz, K. A. Ayub; Palaniswamy, Muthusamy; Jayaraman, Angayarkanni (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of this study was attempted to screen the production of L-asparaginase from bacteria isolated from soil samples and its enzymatic activity. Methods: Screening of L-asparaginase was performed using phenol red indicator growth medium from which the positive strains were chosen based on the colour change. The enzyme production of L-asparaginase was established by submerged fermentation followed by the molecular detection of the efficient bacterial strains. Results: The enzyme production was undertaken by submerged fermentation with the evaluation of enzymatic activity and protein content. This revealed that the strain Escherichia coli CTLS20 produced a higher yield of L-asparaginase (30.22 IU/mg), 16.91 Âµg/ml of protein with the specific activity of 1.787 IU/mg when compared with other bacterial strains. The efficient bacterial strains were also confirmed by 16S rRNA sequence as Escherichia coli, Acinetobacter baumnnii, Klebsiella pneumoniae and the phylogenetic tree construction revealed the evolutionary relationship of the bacterial strains. Conclusion: This study indicated that the bacterial strain E. coli CTLS20 had the ability for the higher production of L-asparaginase. This novel higher yielding bacterial asparaginase is highly desirable as better alternatives in cancer therapy. Keywords: Soil, L-asparaginase, Submerged fermentation, E. coli, Phylogenetic tree